Ortnamnen i J. E. Rietz Svenskt dialekt-lexikon - Thelin, Eva (LexicoNordica, 2019)
In 1862–67 Johan Ernst Rietz published a dictionary of Swedish dialects, which comprised nearly 860 pages. In his dictionary, he included not only dialect words but also 450 place names. This article brings these names into focus and examines what reasons Rietz might have had for including them. How the names are defined and how information about their pronunciation and provenance is conveyed is also analysed.